A Photoaffinity Displacement Assay and Probes to Study the Cyclin‐Dependent Kinase Family. Issue 48 (31st October 2019) - Grant, Emma K.; Fallon, David J.; Eberl, H. Christian; Fantom, Ken G. M.; Zappacosta, Francesca; Messenger, Cassie; Tomkinson, Nicholas C. O.; Bush, Jacob T.
Abstract: The CDK family plays a crucial role in the control of the cell cycle. Dysregulation and mutation of the CDKs has been implicated in cancer and the CDKs have been investigated extensively as potential therapeutic targets. Selective inhibition of specific isoforms of the CDKs is crucial to achieve therapeutic effect while minimising toxicity. We present a group of photoaffinity probes designed to bind to the family of CDKs. The site of crosslinking of the optimised probe, as well as its ability to enrich members of the CDK family from cell lysates, was investigated. In a proof of concept study, we subsequently developed a photoaffinity probe‐based competition assay to profile CDK inhibitors. We anticipate that this approach will be widely applicable to the study of small molecule binding to protein families of interest. Abstract : Selectivity snapshots with PALs : Photoaffinity probes were designed to target the cyclin‐dependent kinase family, and found to competitively enrich CDKs from cell lysates. Subsequently, a biochemical photoaffinity displacement assay was developed to measure compound potency.